Comparative study on sunlight induced surfactants system in photogalvanics for solar energy conversion and storage - Mohan Lal; KM Gangotri (Next Sustainability)
The aim of the study is to harness and store solar energy through photogalvanic (PG) cells. The mixed surfactant pairs, i.e., NaLS+Brij-35 and NaLS+Tween-80, with photosensitizer methylene blue and reductant D-xylose have been used for PG cells. The resulting photoelectrochemical process in photogalvanics leads to energy conversion for sustainable development in the field of solar energy. The electrical outcomes, i.e., VOC, SPP, SPC, SP, and SCE, were studied for a sunlight-induced PG cell for photocatalytic conversion. The observed VOC, SPP, SPC, SP, and SCE with NaLS+Tween-80 surfactant is of the order of 1120 mV, 867 mV 238.00 µA, 206.34 µW, and 1.3012 %, respectively. The observed VOC, SPP, SPC, SP, and SCE with NaLS+Brij-35 surfactant is of the order of 1123 mV, 870 mV, 240.00 µA, 208.80 µW, and 1.3112 %, respectively. Conclusively, PG cells with NaLS+Brij-35 surfactant are better than PG cells with NaLS+Tween-80. This new combination of surfactants still has the scope to achieve the enhanced electrical results of PG cells for sustainable development.